The manager's pocket guide to corporate culture change - Bellingham, Richard (Managers Pocket Guide Series., 2001)
In order to achieve desired transformation in corporate culture, leaders must take a logical and systematic approach to change. The most successful change programs begin with a statement of shared values. Beginning with values ensures that the entire organization puts purpose before action. The Manager's Pocket Guide to Corporate Culture Change provides the essential methods for mobilizing people behind these shared values. It teaches the skills to empower people within defined parameters, the type of support they require for success, and the best ways to recognize individual and team contributions. It also reviews the basic tenets for developing people, creating a learning organization, and provides practical methods for aligning the culture behind the business strategy in order to manage the change. The Manager's Pocket Guide to Corporate Culture Change is easy-to-read, engaging, and interactive. Each skill has an introduction, an overview, the basic idea, an illustration, and an opportunity for the reader to apply the skill.